Section 498, Penal Code (Act 574): An Antiquated Law? - Abdullah, Nor Aini (Journal of Malaysian and Comparative Law, 2019)
The above article is about section 498 of the Malaysian Penal Code. Section 498 reads â€¦ â€œWhoever takes or entices away any woman who is and whom he knows, or has reason to believe, to be the wife of any other man, from that man, or from any person having the care of her on behalf of that man, with intent that she may have illicit intercourse with any person, or conceals, or detains with that intent any such woman, shall be punished with imprisonment for a term which may extend to two years or with fine or with both â€¦â€. It is about an archaic offence which entails in depriving the husband of his proper control over his wife for the purpose of illicit intercourse. Any disposition or consent or willingness on the part of the wife is perfectly immaterial to the guilt of the accused. Thus the literature of this article revolves around this antique provision; and how not or whether not to abolish it or maintain or amend it.